Compound-specific δ15N amino acid measurements in littoral mussels in the California upwelling ecosystem: a new approach to generating baseline δ15N Isoscapes for coastal ecosystems. - Natasha L Vokhshoori; Matthew D McCarthy (PLoS ONE, 2014)
We explored δ(15)N compound-specific amino acid isotope data (CSI-AA) in filter-feeding intertidal mussels (Mytilus californianus) as a new approach to construct integrated isoscapes of coastal primary production. We examined spatial δ(15)N gradients in the California Upwelling Ecosystem (CUE), determining bulk δ(15)N values of mussel tissue from 28 sites between Port Orford, Oregon and La Jolla, California, and applying CSI-AA at selected sites to decouple trophic effects from isotopic values at the base of the food web. Bulk δ(15)N values showed a strong linear trend with latitude, increasing from North to South (from ∼ 7‰ to ∼ 12‰, R(2) = 0.759). In contrast, CSI-AA trophic position estimates showed no correlation with latitude. The δ(15)N trend is therefore most consistent with a baseline δ(15)N gradient, likely due to the mixing of two source waters: low δ(15)N nitrate from the southward flowing surface California Current, and the northward transport of the California Undercurrent (CUC), with (15)N-enriched nitrate. This interpretation is strongly supported by a similar linear gradient in δ(15)N values of phenylalanine (δ(15)NPhe), the best AA proxy for baseline δ(15)N values. We hypothesize δ(15)N(Phe) values in intertidal mussels can approximate annual integrated δ(15)N values of coastal phytoplankton primary production. We therefore used δ(15)N(Phe) values to generate the first compound-specific nitrogen isoscape for the coastal Northeast Pacific, which indicates a remarkably linear gradient in coastal primary production δ(15)N values. We propose that δ(15)N(Phe) isoscapes derived from filter feeders can directly characterize baseline δ(15)N values across major biochemical provinces, with potential applications for understanding migratory and feeding patterns of top predators, monitoring effects of climate change, and study of paleo- archives.